Methodological Development of the Assessment Procedure and of the Course Design «Adaptive Swimming with Dolphins». The Impact on Children with ASD. - A.A. Zykov; A.E. Vasilyeva; E.Y. Davydova (Moscow State University of Psychology and Education, 2021)
Nowadays dolphin-assisted therapy is a method of animal-assisted therapy without a standardized form of conduction and effectiveness assessment. In this paper, a literature review performed on the topic of the effects, impact mechanisms and application area of animal-assisted therapy with dolphins. There is numerous evidence that participation of children with autism spectrum disorders (ASD) in dolphin therapy leads to a decrease in stereotypic behavior, increased concentration, improved speech skills, and stabilization of the emotional state. Nevertheless, in most cases, these results are inconclusive, due to poor control of the influence of side factors. The analysis resulted in the study design of the dolphin-assisted therapy effects on children with ASD, as well as evaluation methods, considering previous research experience and existing criticism of previous findings. The article also includes the hypotheses, goals and objectives description of an upcoming pilot study of the use of directed animal therapy with dolphins.